2013
DOI: 10.1111/jace.12481
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Multicolor Emission and Energy Transfer of Sb3+/Mn2+ Codoped Phosphate Glasses by Design

Abstract: In this work, the luminescent properties of Sb 3+ /Mn 2+ codoped 60P 2 O 5 -40MgO glass are presented. White light photoluminescence combining blue and orange-red light was observed under ultraviolet light excitation. The emission spectra showed that the blue emission intensity of Sb 3+ decreased significantly whereas the red emission intensity of Mn 2+ increased with the increasing concentration of Mn 2+ ions. Meanwhile, by maintaining the concentration of MnO (2.0 mol%) and increasing concentration of Sb 2 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
4
16
0
Order By: Relevance
“…5,6 For instance, enhanced emissions of Sm 3+ and Eu 3+ were observed in self-activated phosphors, exampling as Ca 2 NaMg 2 V 3 O 12 :Sm 3+ , 7 K 2 YZr(PO 4 ) 3 :Eu 3+ , 8 where V 5+ -O 2− and Zr 4+ -O 2− charge transfer (CT) transitions were involved. 13 More interestingly, Masai et al recently reported deep-UV-driven emission properties of SnO-ZnO-P 2 O 5 glasses, and the largest quantum efficiency (QE) among glass materials was observed, which is comparable to those of crystal phosphors such as MgWO 4 . Therefore, it is a challenge to exploit novel sensitizers with highly efficient absorption in UV region.…”
mentioning
confidence: 97%
“…5,6 For instance, enhanced emissions of Sm 3+ and Eu 3+ were observed in self-activated phosphors, exampling as Ca 2 NaMg 2 V 3 O 12 :Sm 3+ , 7 K 2 YZr(PO 4 ) 3 :Eu 3+ , 8 where V 5+ -O 2− and Zr 4+ -O 2− charge transfer (CT) transitions were involved. 13 More interestingly, Masai et al recently reported deep-UV-driven emission properties of SnO-ZnO-P 2 O 5 glasses, and the largest quantum efficiency (QE) among glass materials was observed, which is comparable to those of crystal phosphors such as MgWO 4 . Therefore, it is a challenge to exploit novel sensitizers with highly efficient absorption in UV region.…”
mentioning
confidence: 97%
“…15 Transition metal Mn 2+ can provide a broad emission band in the visible (VIS) range corresponding to d-d transition, and its emission varies from green to red depending on the crystal field. 16 Since the absorption efficiency of d-d transition is low due to the spin-and parityforbidden electricdipole transition, sensitizing ions (Eu 2+ , Ce 3+ , etc.) are often utilized to enhance the emission of Mn 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, RE-free "green" glasses with low-cost are highly favored in the development of novel materials for greenhouses. Interestingly, it is notable that amorphous glasses containing ns 2 -type emission centers (nZ 4), such as Bi 3 þ , Tl þ , Sb 3 þ , and Sn 2 þ , recently received a great deal of attention because of the intense photoluminescence (PL) properties due to for their parity-allowed transitions [13][14][15]. Compared with the site distribution of crystals, amorphous glasses are suitable for ns 2 -type emission centers [14].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it is notable that amorphous glasses containing ns 2 -type emission centers (nZ 4), such as Bi 3 þ , Tl þ , Sb 3 þ , and Sn 2 þ , recently received a great deal of attention because of the intense photoluminescence (PL) properties due to for their parity-allowed transitions [13][14][15]. Compared with the site distribution of crystals, amorphous glasses are suitable for ns 2 -type emission centers [14]. More interestingly, the highest luminescence quantum yield (QY) among amorphous materials was recently obtained in the SnO-P 2 O 5 -ZnO glass system, which is comparable to a phosphor crystal, such as MgWO 4 [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation